Empowering Teachers in Designing Gamification as a Vocational Learning Strategy in Vocational Schools - Jumiati Siska; Liza Yulianti; Muhammad Kristiawan; Afes Agustianza; Destika Rinanda (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: The integration of gamification in education has emerged as an effective strategy to enhance student motivation, engagement, and learning outcomes. However, many vocational school teachers lack the necessary skills and knowledge to design gamified learning experiences that align with the unique characteristics of vocational education.Aims: This paper aims to empower vocational school teachers with competencies in designing gamification-based learning strategies. The scope includes exploring teachers’ understanding of gamification principles, developing their design skills through training and workshops, and assessing the effectiveness of these interventions in enhancing vocational teaching practices.Methods: A qualitative descriptive approach was employed. Teachers participated in hands-on workshops focusing on gamification frameworks, digital tools, and practical design projects tailored to vocational learning contexts. The collected data were analyzed thematically to identify changes in teachers’ knowledge, skills, and confidence.Results: The results indicated that the teacher empowerment program significantly improved teachers’ ability to design gamification-based learning strategies. Teachers demonstrated increased creativity, improved alignment between gamified activities and vocational learning objectives, and greater confidence in using digital tools. Quantitative findings showed that 85% of participating teachers exhibited improved competence after the training program, with average post-test scores increasing from 62.4 to 84.7. Furthermore, 78% of participants reported a high level of readiness to implement gamification in their classrooms.Conclusion: Empowering teachers in gamification design is an effective approach to strengthening vocational education. It enhances teachers’ pedagogical competencies, promotes learner-centered instructional practices, and supports continuous professional development to meet the evolving demands of vocational education.